Towards a measurement of internalization of collaboration scripts in the medical context – results of a pilot study - Kiesewetter, Jan (German Medical Science GMS Publishing House, 2015)
Background: Collaboration as a key qualification in medical education and everyday routine in clinical care can substantially contribute to improving patient safety. Internal collaboration scripts are conceptualized as organized - yet adaptive – knowledge that can be used in specific situations in professional everyday life. This study examines the level of internalization of collaboration scripts in medicine. Internalization is understood as fast retrieval of script information.